Гнездование каравайки в Крыму - Костин, Ю.В. (Вестник зоологии, 1969)
Till 1965 Plegadis falcinellus L. were observed in the Crimea only during their spring flight. In 1965 in the Razdolnoye district of the Crimea this bird was met for the first time in summer in July. In May — June of 1967 on Lebyazhii islands the Karkinitsky bay of the Black Sea)‘ the first seven nests of Plegadis falcinellus L. were found. Conditions of nesting are not usual. The nests are arranged on the ground among brushwood of absinth and dwarfish thin reed.